Indícios de apropriação dos nexos conceituais da álgebra simbólica por estudantes do Clube de Matemática - Oliveira, Daniela Cristina de (2014)
With regard to education, the humanization process, based on the Cultural-Historical Theory and Activity Theory principles, is materialized through the process of appropriation of knowledge historically constructed. So there is the need of organization of institutionalized education, the contents choice and of teaching activities planning that enable individuals be in activity. The Math Club arises in this context as a learning space organized for children in the early years. Learning triggering situations (LTS) have been prepared in search for situations that promote the different knowledge sharing, collectively, mediated by a content. Algebraic conceptual nexus were chosen as the study object of the individuals in the LTS. Thus, we conducted a didatic experiment, assumed to research methodology, with 12 children from 5th grade of elementary school, from a public school in Goiânia, in order to show evidence of appropriation of the conceptuals nexus of symbolic algebra. We seek to understand our research object through oral and written manifestations of the students and their actions, during the teaching and learning process from Math Club. Obtaining empirical data was through audiovisual recordings, observation, field journal, record sheet and circle of conversation. The software webQDA was taken as a further methodological resource to assist in the analysis and organization of qualitatives data. We assume the analysis units concept, proposed by Vigotski, to apprehend research object, namely: the collective actions and reflections on learning space; playfulness as a feature in LTS organization; signs of appropriation of conceptual nexus of symbolic algebra. Conclusively, we inferred that the children showed signs of appropriation of algebraic conceptual nexus, in a process that begins from the representation need of simbolic algebric language for the beginning of a generalization process. However, the product of this process consisted in teaching organization composed of regular movements, from particular to the general, that emphasized, in a way, the generalization and abstraction processes guided by empiricism.